Creating English learning media using Canva: EFL students’ perspective - Sari, Mariska Intan; Utari, Septiya Dwi; Arfiandhani, Puput (Universitas Ahmad Dahlan, 2023)
Learning media are important parts of the teaching and learning process. Using Canva as a tool for creating English learning media is one of the ways EFL students can do when preparing their teaching and learning practices. This study investigates EFL students’ perceptions of the kinds of English learning media created by the EFL students using Canva and the benefits of using Canva as a tool for creating English learning media as perceived by these students. The researchers employed a descriptive qualitative design to achieve the objectives of this study. This study was conducted at a large private university in Yogyakarta, Indonesia. The participants in this study were six EFL students from the 2019 batch. The researchers conducted interviews to gather in-depth experiences of the participants. The findings of this study indicate that EFL students have created seven different types of English learning media using Canva. The English learning media created by EFL students were presentation slides, textbooks, flashcards, video learning, Instagram content, Infographics, and Twibbons. The findings also elaborate on several benefits of using Canva to create English learning media as perceived by the EFL students. The benefits are that Canva is easy to use, provides various templates for various learning media, caters to EFL students’ creativity, saves time for the EFL students in creating teaching media, and allows EFL students to create fun multimodal learning media.